P379 CARDIAC CONDUCTION DISEASE IN YOUNG PEOPLE: DON'T FORGET THE GENES. (18th May 2022) - De Carolis, B; Di Domenico, A; Gualandi, F; Vitali, F; Bertini, M; Guardigli, G; Balla, C
Abstract: Introduction: Heart rhythm disorders in young individuals are often associated with mutations in genes encoding ion channels. A frequently encountered mutation is in the SCN5A gene, which encodes the alpha subunit of the sodium channel. Mutations in this gene can be expressed through a wide spectrum of phenotypic manifestations including rhythm disturbances, structural cardiac changes and/or overlap syndromes (long/short QT syndrome, Brugada syndrome, sinus node syndrome, progressive cardiac conduction disorder, dilated cardiomyopathy and arrhythmogenic cardiomyopathy). Case Report: 23–year–old boy with no relevant history. During the induction of anaesthesia for a surgical intervention of nasal polyposis, episodes of asystole with a maximum duration of about 6 seconds were documented. During the hospital stay, a syncopal episode followed, with electrocardiographic monitoring showing a sinus arrest of approximately 16 seconds (Fig. 1 ). Echocardiography and cardiac resonance ruled out the presence of structural alterations. In view of the documented bradyarrhythmia, the clinical findings and the absence of secondary causes, a dual–chamber pacemaker implant was performed. The patient was subsequently admitted for ectopic atrial tachycardia (Fig. 2 ) symptomatic for heart palpitations, treated with medical therapy. After careful reconstruction of the family tree (Fig. 3 ), a positive family history of bradyarrhythmias emerged (grandfather and sister of the paternal grandfather were pacemaker carriers). A blood sample was taken for genetic analysis and a mutation in the SCN5A gene (ex28 c5207 A>G) was detected. The genetic study was extended to first–degree relatives (still in progress). During follow–up visits the patient reported subjective well–being and at pacemaker interrogation evidence of 29% atrial pacing, in the absence of ventricular pacing. Conclusions: When faced with a young patient with a conduction disorder, once possible secondary causes have been excluded, genetic analysis should be included in routine examinations because it helps to define an adequate clinical–instrumental follow–up and to identify, at an early stage, the possible progression of the disease and/or the onset of concomitant structural heart disease. Family genetic screening is also essential in order to identify patients at risk of developing the disease.